2011
DOI: 10.1097/iae.0b013e31820a68f8
|View full text |Cite
|
Sign up to set email alerts
|

Does Haptoglobin Genotype Affect Early Onset of Diabetic Retinopathy in Patients With Type 2 Diabetes?

Abstract: The Hp genotype apparently plays no role in the development or worsening of proliferative retinopathy in DM2. Hp1-1 may be involved in delaying the onset of diabetes. Hp2-2 may pose a microvascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(60 reference statements)
0
3
1
Order By: Relevance
“…As hyperglycemia-induced oxidative stress in diabetes is central in processes leading to microvascular complications, including retinopathy [86], it would appear possible that risk of retinopathy could differ depending on the Hp genotype. However, results from a recently published study among 98 consecutive adults with type 2 diabetes and either no retinopathy after at least 10 years of diabetes duration or proliferative retinopathy before 10 years following diagnosis showed no increased risk associated with the Hp 2 allele [87]. In this study, an increased risk was shown for neither the development nor the worsening of proliferative retinopathy [87].…”
Section: Haptoglobin Genotype and Diabetic Retinopathycontrasting
confidence: 53%
See 1 more Smart Citation
“…As hyperglycemia-induced oxidative stress in diabetes is central in processes leading to microvascular complications, including retinopathy [86], it would appear possible that risk of retinopathy could differ depending on the Hp genotype. However, results from a recently published study among 98 consecutive adults with type 2 diabetes and either no retinopathy after at least 10 years of diabetes duration or proliferative retinopathy before 10 years following diagnosis showed no increased risk associated with the Hp 2 allele [87]. In this study, an increased risk was shown for neither the development nor the worsening of proliferative retinopathy [87].…”
Section: Haptoglobin Genotype and Diabetic Retinopathycontrasting
confidence: 53%
“…However, results from a recently published study among 98 consecutive adults with type 2 diabetes and either no retinopathy after at least 10 years of diabetes duration or proliferative retinopathy before 10 years following diagnosis showed no increased risk associated with the Hp 2 allele [87]. In this study, an increased risk was shown for neither the development nor the worsening of proliferative retinopathy [87]. To our knowledge, no other studies have to date assessed this association prospectively.…”
Section: Haptoglobin Genotype and Diabetic Retinopathymentioning
confidence: 53%
“…In this study, two studies [13, 14] in the recessive model, allele model, and additive model all showed no heterogeneity of the studies between DR and DWR ( X 2 p = 0.08, I 2 = 68%; X 2   p = 0.11, I 2 = 60%; and X 2   p = 0.07, I 2 = 68%, resp. ); the subtotal effect size OR in this study was 2.23 (95% CI: 0.68, 7.35), 1.74 (95% CI: 0.72, 4.18), and 2.21 (95% CI: 0.66, 7.44), respectively, all suggesting that Hp gene variants were not associated with NPDR (Figure 8).…”
Section: Resultsmentioning
confidence: 51%
“…Two studies [14, 18] in all models showed no heterogeneity of the studies ( X 2   p = 0.29 > 0.1, I 2 = 11%; X 2   p = 0.62 > 0.1, I 2 = 0%; X 2   p = 0.23 > 0.1, I 2 = 30%; X 2   p = 0.37 > 0.1, I 2 = 0%; X 2   p = 0.91 > 0.1, I 2 = 0%; and X 2   p = 0.31 > 0.1, I 2 = 2%), and the subtotal effect size OR in these studies was 0.96 (95% CI: 0.64, 1.43), 0.60 (95% CI: 0.23, 1.57), 0.99 (95% CI: 0.51, 1.93), 0.66 (95% CI: 0.23, 1.88), 0.53 (95% CI: 0.19, 1.52), and 1.19 (95% CI: 0.74, 1.91), respectively, all suggesting that Hp gene variants were not associated with PDR (Figure 9). …”
Section: Resultsmentioning
confidence: 99%